Strengthening Student Resilience: Student-Centered Learning Model in Merdeka Curriculum in Elementary Islamic School - Noptario Noptario; M. Ferry Irawan; Abd Razak Zakaria (Universitas Islam Negeri (UIN) Salatiga, 2024)
Mental health issue among Indonesian students is prevalent. The Indonesian National Adolescent Mental Health Survey reports that over one-third of Indonesian adolescents are grappling with mental health concerns, leading to higher stress levels and negative effect on the academic quality. To address this issue, it is necessary to introduce the concept of resilience to students as a preventive measure against more severe issues. Student-centered learning (SCL) emerges as a viable approach to instilling resilience. Therefore, this research focused on the internalization of resilience through the SCL model in Merdeka curriculum. This qualitative field research involved deputy head of curriculum, the homeroom teacher and students of class 6B. Data were gathered through interviews and observations, and analyzed using thematic analysis. The findings suggest that the SCL model encourages active and enthusiastic student participation. Teachers employ various strategies, such as project-based learning, problem-based learning, technology integration, differentiated learning, and fostering a positive environment, to instill resilience in students. These initiatives empower students to cultivate resilience, equipping them with the essential skills to navigate life successfully in the future. This study concludes that SCL model in Merdeka curriculum can instill resilience in students, thus making students strong and resilient in receiving learning.